Longitudinal Aerodynamic Characteristics of an Aircraft Model with and Without Winglet - Hossain, Md. Altab (2005)
The measurement of aerodynamic forces and moments acting on an aircraft model is important for the development of wind tunnel measurement technology. The primary purpose of wind tunnel measurements over the model for the forces and moments is to predict the performance of the full-scale vehicle. Force measurement techniques in wind tunnel testing are necessary for determining a variety of aerodynamic performance parameters. For three-dimensional aircraft models, forces and moments are usually measured directly using a balance system. The balance mechanically separates the total aerodynamic load on a model into its six aerodynamic components. Two fundamental types of balances, external and internal balances, are used today. External balances carry the loads outside the tunnel before they are measured and internal balances which fit in the model and are arranged to send data out through electrical wires.In this research work, six-component external balance is commissioned and the calibration has been thoroughly checked and the detailed procedure of measurement of aerodynamic forces is recommended. A set of winglet has been designed for the existing aircraft model at the Aerodynamics laboratory of the Aerospace Engineering Department, UPM. Further the aerodynamic forces are measured on the aircraft model having a rectangular wing with and without winglet attached to the model. Tests have been carried out on the aircraft model with and without winglet at the Reynolds numbers 170,000, 210,000 and 250,000. The experimental results show that lift curve slope increases by 1-6% with the addition of certain winglet configurations and at the same time the drag decreases by 20-28% as compared to those for the aircraft model without winglet for the maximum Reynolds number considered in the present study.